Transformation of 3D GPS cartesian coordinates to ED50 using polynomial fitting by robust re-weighting technique - Soycan, M.; Soycan, A. (MANEY PUBLISHING, 2008)
The purpose of this study is the solution of the transformation problem between the GPS networks and old geodetic networks based on the national coordinate system alternatively by a 3-dimensional robust polynomial transformation (3D.R.P.T). This study focuses on and probes 3D similarity (3D.S.T), 3D polynomial transformation with least squares estimate as equal-weighted (L.S.3D.P.T), 3D polynomial transformation based on weight with the inverse of the distances of common points to the centre of gravity (W.L.S.3D.P.T) and robust estimate approaches that are re-weighted and are based on iterative solution. A detailed mathematical model and solution algorithm of the proposed model is given, and it has been applied in a test area covering the city borders of Istanbul for which its results were studied and compared to other three methods.
Keywords: transformation; ED50; polynomial fitting; robust re-weighting; cartesian coordinates; Engineering; Geology; Remote Sensing